PENGEMBANGAN POCKET BOOK BERBASIS LITERASI SAINS MATERI EKOLOGI DAN KEANEKARAGAMAN HAYATI - Abadiyah, Siti Saadatul; Ahied, Mochammad; Wulandari, Ana Yuniasti Retno; Rakhmawan, Aditya; Fikriyah, Aida (Program Studi Pendidikan IPA, Universitas Trunojoyo Madura, 2024)
This study aims to determine the feasibility, readability, and student response to pocketbooks based on scientific literacy on ecology and biodiversity material. The study uses development research with an ADDIE development model. The research samples were 25 students of class VII-I MTsN Bangkalan. The instruments used were the media expert validation sheet, material expert validation, readability questionnaire, and student response questionnaire. The study results showed that: 1) The results of the validity of media experts and material experts with the Gregory test are 1.00 with very valid criteria. 2) The results of pocket book readability obtained a percentage value of 81.62% with very good criteria. 3) Students' responses to the pocketbook obtained a percentage value of 82.19% with very good criteria. The results showed that the use of a pocketbook based on scientific literacy on ecology and biodiversity material is feasible to use in learning.